Optimization of Data Processing of Non-Stationary Processes Based on Setting the Parameters of Fuzzy Models - Makhmudovich, Kholmonov Sunatillo; qizi, Mirsanova Gulbahor Muhammadi (International Journal of Human Computing Studies, 2022)
Scientific and methodological foundations, methods, models and algorithms for processing data of non-stationary objects based on the mechanisms for setting the parameters of fuzzy sets using genetic algorithms have been developed. The processes of transformation of input data into output data are modeled based on the use of the properties of fuzzy sets and functional connections of inputs and outputs. Methods of intellectual analysis and data processing are implemented for forecasting in automated process control systems.